ANALISIS PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KOTA PONTIANAK - Desty Wana; Agnes K. B Mudamakin; Asna Marina (JAKA - Jurnal Jurusan Akuntasi, 2023)
The title of this research is “ Analysis of tax Knowledge, taxpayer Awareness and Tax Sanction Againts Motor Vehicle Taxpayer Complience in Pontianak City”. This study aims to determine the effect of tax knownledge, taxpayer awareness, tax sanctions, on compliance with motor vehicle tax payments in Pontianak city. Sample selection using random sampling method, by distributing quentionsaires directly to respondent at random. The population of this study are taxpayers who are registered in the SAMSAT UPPD Office Region 1 Pontianak City and the sample is taken at least 50 respondent from the population. There are several research method used to achieve the objectives of this study including descriptive statistical analysis, validity test, reliability test, classical assumption test (normaly test, multicollinearity test, heteroscesdaticity test), multiple regression analysis, and t test, taxation does not have a positive effect on the compliance of motorized vehicle taxpayers in the city of Pontianak. Meanwhile, taxpayer awareness and tax sanctions have a positive effect on taxpayer compliance